2011
DOI: 10.1111/j.1747-0285.2011.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Investigations Of Leishmanicidal N‐Benzylcytisine Derivatives

Abstract: In vitro leishmanicidal activity of 16 N-benzylcytisine derivatives has been evaluated using Leishmania donovani axenic amastigotes. In general, halogen (bromo-, chloro-) derivatives appeared to be more toxic against parasites than their parent compounds. Quantum-chemical calculations helped to recognize certain patterns in the structure of frontier orbitals related to bioactivity of compounds. Thus, the presence of halogen atom is shown to have a significant effect on both distribution and the energy of LUMOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…By comparison with N , N -(2-(diethylamino)ethyl)amides, N -(2-(ethylamino)-ethyl)amides were much more active against the four cell lines, in particular against K111 and NCI-H460 ( 14g vs. 14h , 14o vs. 14p , 14q vs. 14r ). On the basis of the crystallographic structure study [ 24 ], the functional group at C-4′ position of pyrrole should be exposed to water. Perhaps the secondary amine structure and low steric hindrance of the terminal ethylamino group of N -(2-(ethylamino)ethyl)amides are favourable for the formation of hydrogen-bonds with water to improve the solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison with N , N -(2-(diethylamino)ethyl)amides, N -(2-(ethylamino)-ethyl)amides were much more active against the four cell lines, in particular against K111 and NCI-H460 ( 14g vs. 14h , 14o vs. 14p , 14q vs. 14r ). On the basis of the crystallographic structure study [ 24 ], the functional group at C-4′ position of pyrrole should be exposed to water. Perhaps the secondary amine structure and low steric hindrance of the terminal ethylamino group of N -(2-(ethylamino)ethyl)amides are favourable for the formation of hydrogen-bonds with water to improve the solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Hrib et al reported that the introduction of chlorine into nemonapride constituted a ubiquitous function-determining domain, while the removal of the chlorine was deleterious to the selectivity among the dopaminergic receptors [ 23 ]. Among leishmanicidal N -benzylcytisine derivatives, the chloro derivative demonstrated 10-fold stronger inhibition ability than others [ 24 ]. On the aromatic ring of arvanil, the replacement of a 3-methoxy group with a chlorine atom increased the capability to inhibit FAAH [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[31] The importance of Cl in drug design is due to its moderate halogen bond acceptor ability and the stability of Cl-C bond in hydrophobic pockets of the biological targets. [62,63] The chemical structure and anticancer activity of this series were assessed in vitro against A549 (adenocarcinomic human alveolar basal epithelial cells), KB (oral epithelial), K111 (melanoma), and NCI-H460 cells (large cell lung cancer), together with the inhibition of VEGFR-2 as compared with sunitinib ( Figure 3 and Table 1).…”
Section: -Substituted Indolin-2-ones Containing the Chloropyrrole mentioning
confidence: 99%
“…[8] Av aluable approacht oo btain novel CQ analogues is representedb yt he assembly of hybrid molecules containing two pharmacophores joined through al inker that should not disturb the interaction of each component with the relevant target. [26] 4) The replacement, in the foregoing compounds, of the NH group with as ulfur bridge (e.g.,c ompounds 22-27;F igure 3), which in addition to decreasing the basicity of the molecule should also increasei ts lipophilicity.T he right balance of these physicochemical characteristics is fundamentalf or the accumulation of the drug in the digestive vacuole and for its association with hematin to inhibit the formation of hemozoin. [11] Particularly interesting hybrid antimalarial agents have been obtained by combining the scaffold of chloroquine and primaquine (PQ) through different linkers (e.g., M).…”
Section: Introductionmentioning
confidence: 99%
“…[25] Interestingly, some N-benzylcytisined erivatives have been recently shown to display activity against the parasite Leishmania donovani. [26] 4) The replacement, in the foregoing compounds, of the NH group with as ulfur bridge (e.g.,c ompounds 22-27;F igure 3), which in addition to decreasing the basicity of the molecule should also increasei ts lipophilicity.T he right balance of these physicochemical characteristics is fundamentalf or the accumulation of the drug in the digestive vacuole and for its association with hematin to inhibit the formation of hemozoin. [4c] 7-Chloro-4-(pyrrolidin-1-yl)quinoline (21), incidentally obtained during the syntheses, was also considered.…”
Section: Introductionmentioning
confidence: 99%